Clinical and Laboratory Findings in Infectious Mononucleosis - Akarsu, Saadet; Demirol, Mustafa; Erensoy, Ahmet; Cakici, Oya; Sari, Yusuf; Arslan, F. Necati; Yildirmaz, Serap (Aves Yayincilik, Ibrahim Kara, 2008)
Aim: To assess the clinical and laboratory characteristics of infectious mononucleosis. Materials and Method: Twenty-one EBV-seropositive patients, who were admitted with different symptoms, were evaluated retrospectively. Results: Mean age was 6.67 years. The most frequent symptoms were abdominal pain (76.2%) and fever (42.8%). Of the patients enrolled in the study, 71.4% had lympadenopathy, 52.4% had hepatomegaly, 47.6% had splenomegaly, and 38.1% had exudative tonsillitis. Mean erythrocyte sedimentation rate was 22.2 mm/hour and C-reactive protein was 30.6 mg/L. We detected atypical cells in 33.3%, leukocytosis in 52.4%, neutropenia in 14.3%, high platelet count (>500,000/mu L) in 19%, thrombocytopenia in 23.8%, elevated liver enzymes in 38.1%, and heterophile antibody positivity in 28.6% of patients. The mean myeloid/erythroid cell ratio in bone marrow aspiration material was 5.3. Conclusion: Infectious mononucleosis is a self-limiting infection and treatment should be mainly supportive.
Keywords: Epstein-Barr virus; infectious mononucleosis; peripheral blood; bone marrow